A NEW APPROACH TO THE SYNTHESIS OF 2-(-3’-OXOBUTHYL)-4-SUBSTITUTED-4-PENTANOLIDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Improved method for obtaining 2-ethoxycarbonyl-2-(3’-oxobuthyl)- and (3’-oxobuthyl)-4-substituted-4-pentanolids by means of sulphuric acid hydrolysis of corresponding 2-(y-chlorcrotyl)-4-substituted-4-pentanolids has been suggested. It has been shown that it is expedient to carry out the hydrolysis by saturated (92–96%) sulphuric acid. Optimal conditions, which provide high yields of goaled products, have been discovered.